Clinical outcomes of antifungal therapy on Candida pulmonary colonisation in immunocompetent patients with invasive ventilation: a systematic review and meta-analysis - Shan Su; Linqi Li; Hongzhong Yang; He-Bin Xie (BMJ Open)
Objective This study aimed to use systematic review and meta-analysis to establish the influence of antifungal therapy on pulmonary Candida colonisation of patients with mechanical ventilation (MV).Design Systematic review and meta-analysis.Data sources An extensive search was undertaken on publications from inception to 25 July 2023, through PubMed, Web of Science, Medline, Embase, China National Knowledge Infrastructure, Wanfang Data and VIP Databases.Eligibility criteria for selecting studies Randomised trials, cohort studies and case-control studies comparing the efficacy of antifungal treatment in immunocompetent patients with pulmonary Candida colonisation after invasive ventilation.Data extraction and synthesis Two reviewers independently extracted the data and assessed the quality of studies. Dichotomous outcomes were expressed as ORs with 95% CIs. Continuous outcomes were expressed as standardised mean differences (SMD) with 95% CIs.Primary and secondary outcome measures The primary outcomes included intensive care unit (ICU), hospital, 28-day, and 90-day mortality. The secondary outcomes included ICU length of stay, MV duration and ventilator-associated pneumonia (VAP).Results Nine high-quality studies were included. According to the data collected from these nine studies, there is no significant evidence showing a difference between the therapy group treated with antifungal drugs and the control group without antifungal drugs in clinical outcomes, including ICU mortality (OR: 1.37; 95% CI 0.84 to 2.22), hospital mortality (OR: 1.17; 95% CI 0.57 to 2.38), 28-day mortality (OR: 0.71; 95% CI 0.45 to 1.14), 90-day mortality (OR: 0.76; 95% CI 0.35 to 1.63), ICU length of stay (SMD: −0.15; 95% CI −0.88 to 0.59), MV duration (SMD: 0.11; 95% CI −0.88 to 1.10) and VAP (OR: 1.54; 95% CI 0.56 to 4.20). Subgroup analysis of different treatment types indicates that the combined effect size is stable and unaffected by different treatment types including inhalation (OR: 2.32; 95% CI 0.30 to 18.09) and intravenous (OR: 0.65; 95% CI 0.13 to 3.34).Conclusion The application of antifungal treatment did not improve clinical outcomes in patients with MV. We do not suggest initiating antifungal treatment in patients with Candida pulmonary colonisation after invasive ventilation.Trial registration number International Prospective Register of Systematic Reviews, CRD42020161138.